ONTOLOGI ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI DALAM PESPEKTIF PENDIDIKAN ISLAM: 1. Mengenal Ontologi dalam Pendidikan Islam 2. Mengenal Epistemologi dalan Pendidikan Islam 3. Mengenal Aksiologi dalam Pendidikan Islam - Qurrotul A’yun Sufyan (Prodi PAI Fakultas Tarbiyah IAI Miftahul Ulum, 2022)
Science is basically a conceptual continuation and the characteristics of curiosity as human nature, curiosity never has limits. Disclosing the basic knowledge used are ontology, epistemology and axiology, or in other words what, how and where science is. In reviewing the three, here tries to display the ontology of science, epistemology of science, and the science of axiology in the perspective of Islamic education. This becomes important to be studied in the realm of Islamic education because it has differences with ontology, epistemology, and axiology studies in other studies. Ontologies in Islamic education try to bring education to know about the nature of everything that is the goal of Islamic education, which is to know the nature of God. In the study epistemology is directed to understand the source of science. Of course, in this case the source of Islamic knowledge is different from the source of knowledge in general. For this reason in this study the Islamic epistemology, especially in Islamic education, tries to provide an explanation of the sources of knowledge in Islamic education which is certainly different from the source of education in general. The axiology of Islamic education in this study is the last to try to see the value of Islamic education as a whole. The aim is to find answers to the uses and values inherent in the context of Islamic education.